Malaysia : Islamic Finance and Financial Inclusion - World Bank (World Bank, Kuala Lumpur, 2020)
The main purpose of this report is to explore the role Islamic finance has played in furthering financial inclusion in Malaysia, with a view to drawing key lessons of experience. Given Malaysia’s success in the development of Islamic finance, these lessons will be useful to policy makers and regulators in other Islamic finance jurisdictions as they make efforts to enhance Islamic financial inclusion. The study will also be relevant to development practitioners involved in providing technical assistance and advisory services to their client countries on different ways to foster financial inclusion and improve the contribution of the financial sector to growth and poverty reduction. The report is composed of five chapters: chapter one presents a macro-level assessment of key inclusion and Islamic finance indicators in Malaysia; chapter two analyses the country’s regulatory structures on which inclusion has been based; chapter three identifies its institutional enablers; chapter four specifies prime consumer protection measures; and chapter five enunciates the impact that digitalization and Islamic financial technology (FinTech) have had in increasing inclusion.